2000
DOI: 10.3139/217.1578
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Rhomboidal Mixing Sections

Abstract: The rhomboidal mixing section is becoming very popular among processors to provide distributive mixing. Currently, several different designs are used but the details of the flow behavior and mixing efficiency is not well understood. This information is needed to be able to design and find the most efficient rhomboid geometry. In this investigation nine different geometries with various pitches (helix of rhomboids) were analyzed using a 3-dimensional boundary element method (BEM). The geometries were compared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…12.37. Rios et al [95] investigated several different configurations of the rhomboid mixing section by changing the two helix angles that define the mixing section. The different sections analyzed are shown in Fig.…”
Section: 434rhomboidal Mixers and Fluted Mixers (Leroy/maddock)mentioning
confidence: 99%
See 2 more Smart Citations
“…12.37. Rios et al [95] investigated several different configurations of the rhomboid mixing section by changing the two helix angles that define the mixing section. The different sections analyzed are shown in Fig.…”
Section: 434rhomboidal Mixers and Fluted Mixers (Leroy/maddock)mentioning
confidence: 99%
“…This device must be well designed for the number of rhomboids in the axial and circumferential directions, length, pitch, and channel depth to create the optimal mixing environment. Using the boundary element method along with experiments Gramann et al [94] and Rios et al [95] studied the rhomboid mixing section. Gramann et al [94] showed with both simulation and a flow visualization experiment that multiple stagnant regions may occur on the sides of the rhomboid depending on its shape.…”
Section: 434rhomboidal Mixers and Fluted Mixers (Leroy/maddock)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rios et al use the boundary element method to compare several different designs of rhomboidal mixing sections with regard to pressure loss and residence time distribution, with a subset of the designs also being subjected to laboratory trials including an analysis of colorant distribution and thermal homogeneity [ 23 , 24 ]. However, the simulation is somewhat simplified and thermal mixing is not considered during design and only measured ‘after the fact’.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, multiple processing steps increase energy usage, manufacturing costs, coordination steps, and time. However, single screw extrusion with new mixing element designs offers several advantages over twin screw extrusion, which has changed the function of single screw extrusion from only plasticating to both plasticating and mixing . For homogeneity, dispersive mixing followed by distributive mixing is optimal…”
Section: Introductionmentioning
confidence: 99%